La protección de los datos de prueba sobre químicos agrícolas en el T.L.C - Cabrera Medaglia, Jorge A. (2014)
This article addresses the provisions of the World Trade Organization Agreement on Data Protection and its legal implications, including the flexibilities granted to the Contracting Parties for its national implementation. It is also presents the national legal framework on this matter. Finally, the article contains an analysis of the Free Trade Agreement provisions on Data Protection and the amendments that it will bring into the current legal system in Costa Rica.